Gangguan Kosmetik Karena Kelainan Pigmentasi Kulit - Hardyanto Hardyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
Patients with pigmentary changes on their skin seek advise primarily for cosmetic reasons, although these are usually asymptomatic and without systemic consequencei. The most common types of pigmentary disturbances are 'freckles, melasma, lentikines, melanoderma, vitiligo and leukoderma.This article discusses normal melanogenesis, and clinical features, pathogenesis and treatment of pigmentary abnormalities of the skin,Patients suffering from pigmentary abnormalities attending the clinic of the Department of Dermatology and Venereology, Gadjah Mada University Hospital, are presented, From 1978 to 1979, 450 patients were noted. 26% males and 74% females, with the following breakdown: 18.2% melasma, 20.2% freckles, 12.4% melanoderma, 6.4% lentigo, 84.7% vitiligo and 8.1% leultoderma . -Key Words: pigmentary abnormalities - hyperpigmentation and hypopigmentation - epidermal melanin unit - hydrocluinon - psoralen